Decorin expression is decreased in first trimester placental tissue from pregnancies with small for gestation age infants at birth. (September 2016) - Murthi, P.; van Zanten, D.E.; Eijsink, J.J.H.; Borg, A.J.; Stevenson, J.L.; Kalionis, B.; Chui, A.K.; Said, J.M.; Brennecke, S.P.; Erwich, J.J.H.M.
Abstract: Fetal growth restriction (FGR) is a leading cause of perinatal morbidity and mortality. FGR pregnancies are often associated with histological evidence of placental vascular thrombosis. The proteoglycans are important components and regulators of vascular homeostasis. Previous studies from our laboratory highlighted mRNA and protein expression differences in placental proteoglycan decorin ( DCN ), within a clinically well-characterised cohort of third-trimester idiopathic FGR compared with gestation-matched uncomplicated control pregnancies. We also showed that decorin contributes to abnormal angiogenesis and increased thrombin generation in vitro . These observations suggest that DCN gene expression may contribute to the etiology of FGR. Small for gestational age (SGA) is frequently used as a proxy for FGR and is defined as a birth weight below the 10th percentile of a birth weight curve. We therefore made use of a unique resource of first trimester tissues obtained via chorionic villus sampling during the first trimester to investigate the temporal relationship between altered DCN expression and any subsequent development of SGA. We hypothesized that placental DCN expression is decreased early in gestation in SGA pregnancies. Surplus chorionic villus specimens from 15 women subsequently diagnosed with FGR and 50 from women with uncomplicated pregnancies were collected. DCN mRNA and DCN protein were determined using real-time PCR and immunoblotting, respectively. Both DCN mRNA and protein were significantly decreased in placentae from first-trimester SGA-pregnancies compared with controls (p < 0.05). This is the first study to report a temporal relationship between altered placental DCN expression and subsequent development of SGA. Highlights: Placental decorin (DCN) expression may contribute to the etiology of FGR. Small for gestation (SGA) is often used as a surrogate for FGR. First trimester placental tissues subsequently developed SGA was investigated. Placental DCN expression is significantly reduced in first trimester SGA at birth. A temporal relationship is observed for placental DCN expression and SGA.